The politics of governing oil after 'best-practice' reforms: Can 'pockets of effectiveness' survive within Uganda's political settlement?. Issue 4 (November 2020) - Hickey, Sam; Izama, Angelo
Highlights: Provides the first analysis of how the new oil governance reforms undertaken in Uganda have been implemented and of their effects on oil governance. Deploys a 'political settlements' analysis to challenge current analyses of how 'best-practice' reforms are likely to unfold in countries with relatively low levels of state capacity and democratisation; this offers deeper insights that go beyond a focus on formal institutions. Shows that developing and maintaining pockets of bureaucratic effectiveness is critical to enabling high-levels of performance. Argues that 'best-practice reforms' can sometimes go with the grain of domestic political settlements and may even enable the progression of a resource nationalist project of oil governance. Abstract: Uganda is frequently lauded for its quality of oil governance, particularly through the political support and autonomy offered to a 'pocket of bureaucratic effectiveness' (PoE) within its oil assemblage. Since 2013, Uganda's adoption of the 'Norway model' has involved breaking up the old PoE and establishing new regulatory and commercial entities. The interaction of these reforms with Uganda's increasingly factionalised political settlement dynamics has reduced the quality of oil governance in certain respects: the process has hollowed-out the policy department and weakened the coherence of oil governance. However, Uganda's earlier investment in PoE building has enabled it to manage the process better than expected, often through informal practices. We show that Uganda adopted the reforms willingly and has moved to build new regulatory and commercial PoEs that fit with its resource nationalist approach to oil governance. This challenges the notion that best-practice reforms inevitably involve the imposition of neoliberal modes of governmentality that go 'against the grain' of domestic political settlements. We reaffirm the critical importance of PoEs to oil sector governance in Africa, and tentatively support the claim that they are more likely to be sustained where power is concentrated and where paradigmatic ideas align with resource nationalism.